Наказ як підстава для призначення на посаду поліцейського - Худякова, О. В.; Khudiakova, O. V. (Право і Безпека. - 2016. - № 2 (61). - С. 99–102, 2016)
Визначено особливості наказу про призначення на посаду як підстави виникнення трудових правовідносин із поліцейськими. Вказано, що цей наказ в одних випадках виконує роль одиничного юридичного факту, виключно з яким пов’язується виникнення трудових правовідносин із поліцейськими, а в інших випадках є елементом юридичного фактичного складу поряд із рішенням поліцейської комісії за результатами конкурсу та/або контрактом. Надано пропозиції з удосконалення закону України «Про Національну поліцію» від 2 липня 2015 року № 580-VIII.

The features of the order for appointment on a position as grounds of the employment legal relations with police officers have been determined. It has been indicated that such an order in some cases serves as a single legal fact, which is exclusively associated with the employment legal relations with police officers, and in other cases is an element of the legal actual structure along with the decision of the Police Commission according to the results of the contest and / or contract. But in any case, an order for appointment on a position of a police officer completes the chain of the relevant legal facts. The propositions to improve the Law of Ukraine «On the National Police» dated from July 2, 2015 No. 580-VIII have been provided. In particular, it is offered to consolidate there a separate Article entitled «An Order for Appointment on a Position of a Police Officer» with the following content: «The order for appointment on a position must indicate: 1) first name, middle name, last name of a citizen of Ukraine appointed for the position of a police officer; 2) the name of the position indicating the unit of the National Police of Ukraine, which a police officer will hold; 3) the date of commencement of duties, and in the case of term appointment the duration of this period and the reasons for term appointment under this Law; 4) conditions of payment. A copy of the order for appointment on a position is provided for a police officer, the other copy is kept in his / her personal file».

Определены особенности приказа о назначении на должность как основания возникновения трудовых правоотношений с полицейскими. Указано, что такой приказ в одних случаях исполняет роль единичного юридического факта, исключительно с которым связывается возникновение трудовых правоотношений с полицейскими, а в других случаях является элементом юридического фактического состава вместе с решением полицейской комиссии по результатам конкурса и/или контрактом. Даны предложения по усовершенствованию закона Украины «О Национальной полиции» от 2 июля 2015 года № 580-VIII.
An order as a ground for appointment on a position of a police officer
Приказ как основание для назначения на должность полицейского
Худякова, О. В. Наказ як підстава для призначення на посаду поліцейського / О. В. Худякова // Право і Безпека. - 2016. - № 2. - С. 99-102.
Худякова О. В. "Наказ як підстава для призначення на посаду поліцейського." Право і Безпека 2 (2016): 99-102.
Khudiakova, O.V. (2016), “An order as a ground for appointment on a position of a police officer” [“Nakaz yak pidstava dlia pryznachennia na posadu politseiskoho”], Pravo i Bezpeka, No. 2, pp. 99–102.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; органы внутренних дел; поліція; наказ; поліцейський; призначення на посаду; трудові правовідносини; трудовий договір; контракт; конкурс; order; police officers; police; appointment; labor legal relations; employment contract; agreement; contest; полиция; приказ; полицейский; назначение на должность; трудовые правоотношения; трудовой договор; контракт; конкурс